Detection of the progenitors of Be X-ray Binaries. Issue Volume 14:Issue S346(2019) (August 2018) - Gies, Douglas; Wang, Luqian; Peters, Geraldine
Abstract: A recent survey of the far-ultraviolet spectra of 264 B-emission line stars has revealed 16 systems with hot companions that are the stripped down remains of a former mass donor star. Some of these will probably become Be + neutron star X-ray binaries in the future. The actual numbers of such systems may be large, because the detected systems have companions that occupy the brief and bright, He-shell burning stage of evolution.